THE EFFECT OF THE USE OF PRODUCTION FACTORS ON THE PRODUCTION OF CARROT FARMING IN SEMBALUN DISTRICT - zulkarnaen Zulkarnaen; Rizal Ahmadi; Rini Winarti (Fakultas Pertanian, Universitas Gunung Rinjani, 2024)
Efficient management of production factors is crucial to increase carrot production and farmers' income in Sembalun Sub-district. By effectively managing these factors, such as optimising land use, ensuring adequate seed availability, reducing pesticide use, and addressing labour shortages, farmers in Sembalun Sub-district can potentially increase carrot production and improve their overall income. This study aims to determine the effect of the use of production factors on carrot farming production in Sembalun District, East Lombok Regency. This research uses descriptive method by collecting data using survey techniques and direct interviews. Determination of the area by purvosive sampling by selecting three villages as the research area, consisting of Sembalun Bumbung, Sembalun Lawang, and Sembaluln Timba Gading. Respondents in this study were farmers who planted carrots on rice fields in the 2022-2023 growing season, namely 30 people who were determined by qouta sampling, while determining the number of respondents for each village was determined by proportional random sampling The results of multiple linear regression analysis obtained F count 30.199 and F table 2.759. At a real level of 0.05 (5%). This means that the results of the analysis obtained F count is greater than F table, where changes in the use of production factors as a whole have a real effect on production. The results of further tests using t-tests of land production factors obtained t-count (6.405), seeds (2.254) and labour (3.019)> from t table 1.71 which means that the production factors of land, seeds, fertilizers and labour have a real effect on production (Y).